Applied business statistics making better business decisions - Black, Ken., author (John Wiley & Sons, 2013)
Black's latest outstanding pedagogy of Business Statisticsincludes the use of extra problems called "Demonstration Problems"to provide additional insight and explanation to working problems,and presents concepts, topics, formulas, and application in amanner that is palatable to a vast audience and minimizes the useof "scary" formulas.
Preface xvii About the Author xxvii INTRODUCTION 1 What Is Statistics 02 Decision Dilemma: Statistics Describe the State of Business in India s Countryside 03 2 Visualizing the Data 18 Decision Dilemma: Container Shipping Companies 19 3 Describing Data Through Statistics 52 Decision Dilemma: Laundry Statistics 53 5 Discrete Probability Distributions 142 Decision Dilemma: Life with a Cell Phone 143 6 Continuous Probability Distributions 184 Decision Dilemma: The Cost of Human Resources 185 7 Distributions of the Sample Mean and Sample Proportion and Sampling Techniques 222 Decision Dilemma: What Is the Attitude of Maquiladora Workers? 223 8 Estimating Parameters for Single Populations 256 Decision Dilemma: Compensation for Purchasing Managers 257 9 Testing Hypotheses about Single Population Parameters 294 Decision Dilemma: Word-of-Mouth Business Referrals and Influentials 295 10 Analyzing the Differences in Two Populations 348 Decision Dilemma: Online Shopping 349 11 Analysis of Variance 408 Decision Dilemma: Job and Career Satisfaction of Foreign Self-Initiated Expatriates 409 12 Introduction to Regression Analysis and Correlation 470 Decision Dilemma: Predicting International Hourly Wages by the Price of a Big Mac 471 13 Basic Multiple Regression Analysis 522 Decision Dilemma: Are You Going to Hate Your New Job? 523 14 Advanced Multiple Regression Analysis 552 Decision Dilemma: Determining Compensation for CEOs 553 15 Forecasting 602 Decision Dilemma: Forecasting Air Pollution 603 16 Chi-Square Analysis 658 Decision Dilemma: Selecting Suppliers in the Electronics Industry 659 17 Analyzing Data Using Nonparametric Statistics 684 Decision Dilemma: How Is the Doughnut Business? 685 18 Quality 734 Decision Dilemma: Italy s Piaggio Makes a Comeback 735 19 Decision Analysis C19-2 Decision Dilemma: Decision Making at the CEO Level C19-3 APPENDICES A Tables 779 B Answers to Selected Odd-Numbered Quantitative Problems 819 GLOSSARY 829 INDEX 839 SUPPLEMENTS 1 Summation Notation S1-1 2 Derivation of Simple Regression Formulas for Slope and y Intercept S2-1 3 Advanced Exponential Smoothing S3-1 Exponential Smoothing with Trend Effects: Holt s Method S3-1 Exponential Smoothing with Both Trend and Seasonality: Winter s Method S3-2 Some Practice Problems S3-5
Includes index.
Keywords: Commercial statistics; Economics -- Statistical methods; Management -- Statistical methods